Limited Diversity among Human Isolates of Bartonella henselae - Dillon, B. (American Society for Microbiology (ASM), 2002)
A study of 59 isolates of Bartonella henselae reveals relatively limited diversity among those of human origin (n = 28). Either of two distinct alleles of both gltA and 16S ribosomal DNA (rDNA) was found in all isolates, with a high level of congruity between 16S and gltA inheritance among proven human pathogens. Human isolates from all over Eastern Australia were most commonly 16S rDNA (Bergmans) type I, with the same gltA allele as the type strain (Houston-1). Comparable feline isolates were more commonly 16S type II, with less congruity of inheritance between 16S and gltA alleles. Previously described arbitrarily primed PCR and EagI-HhaI infrequent restriction site PCR fingerprinting techniques separated Bartonella species effectively but lacked discriminating power within B. henselae. Examination of the 16-23S intergenic spacer region revealed for several strains several point mutations as well as a repeat sequence of unknown significance which is readily detected by HaeIII restriction fragment length polymorphism analysis. The bacteriophage-associated papA gene was present in all isolates. Enterobacterial repetitive intergenic consensus PCR proved to be a useful and robust typing tool and clearly separated human isolates (including imported strains) from the majority of feline isolates. Our data are consistent with published evidence and with previous suggestions of intragenomic rearrangements in the type strain and suggest that human isolates come from a limited subset of B. henselae strains. They strengthen arguments for careful exploration of genotype-phenotype relationships and for the development of a multilocus enzyme electrophoresis and multilocus sequence typing-based approach to the phylogeny of B. henselae.